Penatalaksanaan Fisioterapi pada OA Genu Bilateral: A Case Report - Husain, Sri Mulyani (Journal of Health and Therapy, 2023)
Osteoarthritis is a degenerative disease whose cases are the most common globally. Based on radiological findings, it was found that 70% of patients aged over 65 years suffer from osteoarthritis globally. This problem develops progressively which is characterized by degeneration of joint cartilage so that it can cause limitations in functional activities. A 79-year-old woman complained of motion pain in both knees. This has been felt for 13 years especially when bending the knees and standing for long periods of time. When walking there is a sound in both knees. The result of the doctor's diagnosis was that the patient had bilateral genu OA. The patient has received knee fluid injections several times and has been taking pain medication frequently to date. In addition, the patient also underwent surgery on the spine on November 13, 2020. Physiotherapy in this case was only carried out for 3 meetings. Patients were given programs such as ROM exercise, strengthening, stretching, myofascial release, and gait training. The results of the evaluation for 3 times of therapy showed that there was a decrease in pain intensity, and the risk of falling as well as an increase in ROM, muscle strength, and functional index. Based on the results of supporting examinations, including severe OA due to high pain intensity, stiffness and crepitus sounds when performing flexion-extension movements coupled with predisposing factors, namely obesity that has been experienced for years without any medical action. Based on this, of course, the potential problems that occur have greatly affected not only the knee aspect but have affected other regions such as back and spinal aspects, reduce the risk of falling and can increase ROM, muscle strength, and functional index.